Legacies of the Magdalen Laundries : Commemoration, gender, and the postcolonial carceral state - Pine, Emilie; McAuliffe, Mary (Lecturer in women's studies); Haughton, Miriam (Book collections on Project MUSE., 2021)
This collection raises incisive questions about the links between the postcolonial carceral system, which thrived in Ireland after 1922, and larger questions of gender, sexuality, identity, class, race and religion. This kind of intersectional history is vital not only in looking back but, in looking forward, to identify the ways in which structural callousness still marks Irish society. Essays include historical analysis of the ways in which women and children were incarcerated in residential institutions, Ireland's Direct Provision system, the policing of female bodily autonomy though legislation on prostitution and abortion, in addition to the legacies of the Magdalen laundries. This collection also considers how artistic practice and commemoration have acted as vital interventions in social attitudes and public knowledge, helping to create knowledge and re-shape social attitudes towards this history.